2003
DOI: 10.3748/wjg.v9.i8.1804
|View full text |Cite
|
Sign up to set email alerts
|

Contractile effects and intracellular Ca2+signalling induced by emodin in circular smooth muscle cells of rat colon

Abstract: Emodin has a direct excitatory effect on circular smooth muscle cells in rat colon mediated via Ca(2+)/CaM dependent pathways. Furthermore, emodin-induced peak [Ca(2+)]i increase may be attributable to the Ca(2+) release from IP(3) sensitive stores, which further promote Ca(2+) release from ryanodine-sensitive stores through CICR mechanism. Additionally, Ca(2+) influx from extracellular medium contributes to the sustained increase in [Ca(2+)]i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Ma had proved that exposure of smooth muscle cells to emodin induced an increase in [Ca 2ϩ ]i, and the resultant rising in [Ca 2ϩ ]i was a biphasic rise in [Ca 2ϩ ] consisting of a rapid, transient peak followed by a decline to sustained level that remained elevated above baseline [11]. It is considered the main mechanism for emodin to elevate Ca 2ϩ in SMCs in the physiological conditions via IP 3 route.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Ma had proved that exposure of smooth muscle cells to emodin induced an increase in [Ca 2ϩ ]i, and the resultant rising in [Ca 2ϩ ]i was a biphasic rise in [Ca 2ϩ ] consisting of a rapid, transient peak followed by a decline to sustained level that remained elevated above baseline [11]. It is considered the main mechanism for emodin to elevate Ca 2ϩ in SMCs in the physiological conditions via IP 3 route.…”
Section: Discussionmentioning
confidence: 96%
“…The contractions of SMCs of the colon were measured using computerized image micrometry as described previously [11]. Briefly, the cell suspensions of 0.25-ml consisting of 1 ϫ 10 4 cells were added to 0.1 ml of the solutions containing the test agents.…”
Section: Measurement Of Smcs Contractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contractile response after each agent was defined as the decrease in the average length of the 50 cells and expressed as a percentage of the length before agent administration (17,18).…”
Section: Measurement Of Smooth Muscle Cell Contractionmentioning
confidence: 99%
“…First, it has been shown that emodin enhanced the function of small intestinal peristalsis through triggering the release of motilin and Ach and inhibiting the secretion of somatostatin [3,4]. Secondly, emodin directly contracts the colon smooth muscle by elevating the intracellular Ca 2+ concentration, through Ca 2+ influx from extracellular medium and Ca 2+ release from intracellular stores [5,6]. Furthermore, it has been reported that emodin enhanced colon peristalsis by inhibiting voltagedependent K + current [2].…”
mentioning
confidence: 99%